Rethinking classroom management : strategies for prevention, intervention, and problem solving - Belvel, Patricia Sequeira (Thousand Oaks, California : Corwin Press, 2010)
Provides new real-life examples, intervention techniques, and ready-to-use worksheets for addressing potential problems before learning is disrupted and demonstrates ways to foster student leadership in your classroom.
Part I. Rethinking Our Role in the Classroom -- Part II. The Four ``Ps'' of Prevention: Personal, Prerequisites, Parameters, and Participation -- Part III. Intervention Techniques and Problem-Solving Strategies.
Includes bibliographical references and index.
Keywords: CLASSROOM MANAGEMENT